(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Semirechye’s songs collection begins with the expedition of A. Divaev and I.Zhansugurov in 1920 y. They collected materials on folklore, which amounted to 68 notebooks. I.Zhansugurov in his article «Song, the sing ers» drew attention to the link songs with specific geographical position of the edge. A folklorist M. Zholdasbekov was the first who published the such prominent singers of Zhetysu as serі Sauytbek Ұsaұly, Dәuren and Қyrmyzy, Zhidebay, Қayraқbay, Balқybek, Sauytbek, Әldіbay Bekқұly. These folk singers were called the «Sala Ashanyң alty». A folklorist A. Za taevich was the first who published 100 songs of his native region in the book «500 songs». The group of folkloristsresearches, led by composer E. Rakhmadiyev and musicologist A. Temirbekova collected more than 1,000 phono materials in19581959y.y Also the collecting folk materials has been carried out in different years by such researchers of the Conserva tory Science Laboratory as Yerzakovich B., A. Serikbaev, Rayymbergenov A., G. Omarov S. Elemanova, S. Қaliev. However, only with the collecting activities of B. Muptekeev and his ethnographic collection «Zhetysu auen deri» has been created the ground for the full study of the local tradition. The current article is devoted to the musical features of domestic songs of Zhetysu.